Awareness of energy drink intake guidelines and associated consumption practices: a cross-sectional study. (December 2015) - Peacock, Amy; Droste, Nicolas; Pennay, Amy; Miller, Peter; Lubman, Dan; Bruno, Raimondo
Abstract Background Despite concern regarding harms of energy drink (ED) consumption, no research has been conducted to determine awareness and compliance with ED intake guidelines displayed on product packaging in Australia (a novel approach internationally). Methods A convenience sample of 1922 people completed an online survey. Participants reported their knowledge of maximum recommended daily ED intake according to Australian guidelines. Results Guideline awareness was reported by 38, 23 and 19 % of past year consumers, lifetime, and non-consumers, respectively. Amongst past year consumers, 'accurate estimators ' reported greater ED intake and were more likely to exceed intake guidelines and consume alcohol mixed with ED (AmED). After controlling for demographics and frequency of use, guideline awareness predicted increased likelihood of exceeding guidelines in ED sessions, but was not associated with exceeding ED guidelines in AmED sessions. Conclusions Australia is considered to have the most stringent regulatory approach to EDs internationally. However, advisory statements are not associated with greater awareness and compliance with intake guidelines. Failure to comply with standards for efficacious product labelling, and absence of broader education regarding guidelines, needs to be addressed.